An analytical model of SPL-Feed-Forward OBS core nodes with mixed renewal and poisson process inputs. - Chương, Đặng Thanh; Lợi, Vũ Duy; Nhật, Võ Viết Minh (Journal of Computer Science and Cybernetics, 2012)
Evaluating the performance of contention problem in OBS networks for the case of Poisson traffic is proposed. In this paper, we analyse an approximate model for input process with mixed renewal and Poisson, specifically treating the renewal process of Interrupted Poisson Process (IPP). A mixed system of renewal and Poisson process inputs are analyzed for OBS core nodes with the SPL-Feed-Forward architecture. Approximate formulas of the mean delay and loss probability for the respective inputs are presented in simple closed form.